Alfred Simon Diban Ki-Zerbo Project : images and sounds of the collective memory and the identity of a Church (1915- 2015) - (:unkn) unknown (My University, 2023)
Founded by the White Fathers, the Fathers of the African Missions of Lyon and the Redemptorist Fathers, the Church of Burkina, which, in two thousand and twenty-five, will celebrate its jubilee of one hundred and twenty-five years, finds the sources of its history in the diaries of the missionaries, in ethnographic films, in oral accounts of the first Christians, in research project reports carried out by students in the major seminaries of Saint Peter - Claver of Koumi, Saint - John the Baptist of Wayalghin, Saint - Pierre, Saint - Paul de Kossoghin in Ouagadougou, etc. To rewrite the history and the collective memory of this Church and of the evangelization of Burkina, it is then necessary to probe these different sources. But can this history be reconstituted without taking into account the history of the country itself?This "Alfred Simon Diban Ki-Zerbo Project" is an attempt at an audiovisual and digital writing of the history of the Church of Burkina Faso, the history of colonization and of the first Christians of Burkina Faso from the analysis of collected sound and visual sources. From specific questions, the project consists in examining the archives of the dioceses and parishes of the Church Family of Burkina, those of the Missionaries of Africa in Rome, the archives of the African Cinematheque of Ouagadougou in Burkina Faso (especially on the colonial archives and those of theRTB), as well as other documentary collections (private, family or association owned archives, etc.), targeting the period of 1915 which marked the beginning of a popular uprising against the colonizer and the missionaries to the period of 2015 which also marked the culmination of another popular uprising against President Blaise Compaoré after his 27 years in power.Concretely, this project is a reading "against the current" of the colonial, ecclesial and national archives from 1915 to 2015. It is a survey that requires a multidisciplinary approach and looks into the n
Keywords: African Research